The principle of irony and banter in jeff duham's stand-up comedy entitled spark of insanity : meet achmed the dead terrorist X 9 1992 ) - Imam Mahroja Hakim (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/irh,c.1